Meningkatkan Kemampuan Membaca Permulaan dengan Menggunakan Aplikasi Game Edukasi Secil bagi Anak Disabilitas Intelektual Ringan - Kurniati, Retno; Damri , Damri; Zulmiyetri, Zulmiyetri; Handayani, Endang Sri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is based on field findings that show the still low initial reading skills of students with mild intellectual disabilities in grade V at SLB Negeri Muaro Jambi. The main objective of this study is to examine the effectiveness of using the Secil Educational Game application in optimizing initial reading skills for the students. The research design used is Classroom Action Research (CAR), which is reflective and collaborative. The research subjects involved two students with intellectual disabilities, identified as MR and MD. Data collection techniques were carried out through observation, tests, and documentation. Data analysis was conducted qualitatively through data reduction, data presentation, and drawing conclusions. The research results showed a significant improvement in reading ability. Based on the initial data (pre-test), the scores obtained were 35% for MR and 30% for MD. After the intervention in Cycle I, reading ability increased to 63% for MR and 55% for MD. This achievement continued to develop in Cycle II with final results reaching 88% for MR and 82% for MD. Cumulatively, MR's reading ability increased by 53% and MD increased by 52%. Therefore, it can be concluded that the use of the Secil Educational Game media is effective in improving initial reading competence for children with intellectual disabilities.